Learning Guidance in Creating Interest in Reading, Memorizing and Writing the Qur'an in Students of SDN II Jayalaksana Kedokan Bunder Indramayu - Ahmad Khotibul Umam; Didik Himmawan; Jihan Fatmah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This research aims to provide skills training in the religious field, such as reading, writing and memorizing verses of the Al-Qur'an at SDN II Jayalaksana School. The method used in this research is a qualitative descriptive method. The sample from this research was taken as 10 % of the 180 students at SDN II Jayalaksana for the 2023/2024 academic year and a sample of 30 students was obtained. The data collection technique used was an attitude scale and pretest-posttest questions. The results of the analysis from research data processing show that the school's efforts to increase students' reading of the Al-Qur'an at SDN II Jayalaksana Indramayu Teaching religious education is the main personal learning of course has the consequence that the teacher's responsibility, apart from being an educator and leader, is also as a guide for his students. , especially in increasing students' interest in reading the Koran.